Efektivitas Pembelajaran Tatap Muka Terbatas Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Matematika - Nasrudin, Jafar; Yohanie, Dian Devita; Katminingsih, Yuni; Handyani, Aprilia Dwi (Efektor, 2022)
The government made a policy in education sector that is limited face-to-face learning (TMT) in line with declreasing in cases of COVID-19, which previously carried out online learning. The purpose of this study is to know whether limited face-to-face learning can improve students achievement in mathematics and is more effective than online learning in tenth grade students of OTKP department at vocational high school 2 PGRI Kediri. The study used quantitative research with pre-experimental design in the form of one-group pretest-posttest design. The techniques that researchers use for sampling techniques is simple random sampling. The determination of samples regardless of population strata is 35 students. Data collection techniques through pretest and posttest implemented before and after face-to-face learning in the form of learning outcomes ability test on inverse mathematics and function composition. Data analysis used SPSS 20 for windows. Hypothesis test through paired-samples T-test, which compares the average of two variables in a single sample group. The result of this study showed that average students’ achievement got improved amount of 14,857 and the significant value was 0,000 or (p<0,05). Thus, it can be concluded that average of students achievement in mathematics subject after joining the limited face-to-face learning is increase.